2019
DOI: 10.1039/c8fo02009d
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a new natural gastric lipase inhibitor from star anise

Abstract: The flavonoid myricitrin-5-methyl ether is a potential drug candidate as a gastric lipase inhibitor for the treatment of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…This effect may be due to the enhancement of TG-rich lipoproteins elimination through the improvement of lipoprotein lipase activity, and the enhancement of the uptake of TG carried in VLDL by peripheral organs [39]. Another mechanism may be related to the regulation of intestinal uptake of TG mediated by pancreatic lipase that catalyzes the hydrolysis of TG to mono-and diglycerides, which are uptaken by the intestinal cells [40]. Although the direct implication of TG in atherosclerosis is not confirmed yet, it has been reported that the reduction of serum TG level is effective in preventing hyperlipidemia and treating heart diseases [41].…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be due to the enhancement of TG-rich lipoproteins elimination through the improvement of lipoprotein lipase activity, and the enhancement of the uptake of TG carried in VLDL by peripheral organs [39]. Another mechanism may be related to the regulation of intestinal uptake of TG mediated by pancreatic lipase that catalyzes the hydrolysis of TG to mono-and diglycerides, which are uptaken by the intestinal cells [40]. Although the direct implication of TG in atherosclerosis is not confirmed yet, it has been reported that the reduction of serum TG level is effective in preventing hyperlipidemia and treating heart diseases [41].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, KAE showed reliable inhibitory effects against C. rugosa and C. albicans lipases [21,22]. A recent report described a possible covalent bound created between a gastric lipase and the rhamnosylated myricetin [48]. Molecular docking modeling indicated that the hydroxy group of the catalytic Ser153 residue of gastric lipase lead to a nucleophilic attack on the mentioned flavonol, which induced the addition of 1,4 nucleophilic on the double bound to form an enol function.…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be due to the improved elimination of triglyceride-rich lipoproteins through the improved activity of lipase lipoproteins and improved absorption of triglycerides transported in VLDL by peripheral organs [37]. Another mechanism may be related to the regulation of intestinal uptake of TG mediated by pancreatic lipase that catalyzes the hydrolysis of triglycerides into mono-and diglycerides, which are captured by intestinal cells [38]. Although the direct involvement of TG in atherosclerosis is not yet confirmed, it has been reported that reducing serum TG levels is effective in preventing hyperlipidemia and treating heart disease [39].…”
Section: β-Carotene Bleaching Testmentioning
confidence: 99%